Multigroup Analysis Eastern Indonesian Millenial Behavior in Using Digital Bank - Moh Agus Nugroho; Wahyudi Rusdi (Pusat P2M Politeknik Negeri Batam, 2023)
Transaction value at digital banks grew by around 50.3 percent to 34.3 trillion rupiah when compared to April 2021, digital banks increased deposit interest rates to 7%. This figure is higher than commercial banks which are only 0-4%. This study examines more deeply whether East Indonesian millennials consider LPS Lebel in using and saving at digital banks. East Indonesia was chosen because the number of financial literacy is quite low. The data analysis method uses SEM-PLS and uses a gender and regional/domicile multigroup test, a use analysis of 125 respondents spread across 12 provinces in Eastern Indonesia. The results of the analysis explain that the LPS label variable (LL) and the deposit interest rate (TB) have a positive effect on the interest of Eastern Indonesian millennials in saving at digital banks. However, 88% of Eastern Indonesian millennials do not know exactly what percentage of interest is guaranteed by LPS. In addition, multigroup analysis explains that gender is not an influence on the interest of East Indonesian millennials in saving at digital banks. Meanwhile, the domicile or place of residence between respondents on the island of Sulawesi and outside the island of Sulawesi also does not have a difference